Proportional Feedback Control of Turbulent Flow Over a Circular Cylinder Using Low-Pass Filtered Sensing Velocity 저주파 통과 필터 처리된 센싱 속도 기반 원형 실린더 주위 난류 유동의 비례 되먹임 제어 - Yun, Jinhyeok; Lee, Jungil (Transactions of the Korean Society of Mechanical Engineers, B, 2023)
In this study, we perform a proportional control of turbulent flow over a circular cylinder using the low-pass filtered sensing velocity in the wake. Blowing/suction actuations, acting as control inputs, occur on the cylinder surface near the flow separation, with magnitudes proportional to the filtered transverse sensing velocity. The use of low-pass filters is to remove high-frequency components of the sensing velocity caused by turbulence. Both first and second-order low-pass filters are examined by conducting large eddy simulations of flow over a circular cylinder at Re = 3,900. The results show that the performance of the 1st order low-pass filter in reducing drag and lift fluctuations is better than that of the 2nd order low-pass filter, and is comparable to that of a time-averaged sensing velocity. The control using the 1st order low-pass filter achieves maximum reductions of drag and lift fluctuations by about 11% and 61%, respectively.
Keywords: A circular cylinder; Control inputs; Cylinder surface; High frequency components; Higher-frequency components; Low-pass; Low-pass filters; Proportional control; Proportional feedback; Proportional feedback control; A Circular Cylinder; Low-Pass Filter; Proportional Feedback Control; Turbulent Flow